Joint Impact Assessment of CTA's support to NARI (2008-2014) - Komolong, Birte; Makambo, Maxie (Technical Centre for Agricultural and Rural Cooperation, 2020)
The partnership, spanning ten (10) years, between the Technical Centre for Agricultural and Rural Cooperation (CTA) and the National Agricultural Research Institute (NARI) of Papua New Guinea has been fruitful. CTA, in fulfilling its mandated function, has been supporting a partner organisation in the Pacific Region and NARI, on the other part, has been a successful recipient of CTA’s support and making good use of the invaluable support offered by CTA.